Securing Network Time Protocol. - STENN, HARLAN (Communications of the ACM, 2015)
The article discusses network time protocol. Commentary is presented on the introduction in 1980 of version 1 of NTP by David L. Mills of the University of Delaware, features included in subsequent updates and upgrades, and the role of volunteers in maintaining NTP. Particular consideration is given to addressing NTP abuse vector problems. The author describes how to disable the most important NTP abuse vectors for various versions of NTP including versions 4.2.6 through 4.2.7p27 by adding appropriate lines to the ntp.conf file.